Toxicity assessment of a phase III study evaluating FEC-Doc and FEC-Doc combined with gemcitabine as an adjuvant treatment for high-risk early breast cancer: the SUCCESS-A trial = Toxizitätsbewertung einer Phase-III-Studie von FEC‑Doc und FEC‑Doc plus Gemcitabin als adjuvante Therapie von Hochrisiko-Patientinnen mit Brustkrebs im Frühstadium : die SUCCESS-A-Studie - Schröder, Lennard; Rack, B.; Sommer, H.; Koch, J. G.; Weissenbacher, T.; Janni, W.; Schneeweiss, Andreas; Rezai, M.; Lorenz, R.; Jäger, B.; Schramm, A.; Häberle, L.; et al. (Geburtshilfe und Frauenheilkunde, 2016)
This paper aims to evaluate the toxicity profile of additive gemcitabine to adjuvant taxane-based chemotherapy in breast cancer patients.
Gesehen am 22.05.2020